Analisis Kemampuan Literasi Matematika Siswa dalam Menyelesaikan Soal Trigonometri ditinjau dari Gender di SMK Sunan Giri - Amin, Badri; Anas, Aswar; Sujiwo, Dimas Anditha Cahyo (Universitas Islam Jember, 2025)
This research aims to determine students' literacy skills in solving trigonometry story questions at Sunan Giri Vocational School class X in terms of gender. Literacy is not only about the technical ability to read and write but also about understanding and using information effectively to achieve goals. The type of research used in this study is qualitative research with a descriptive approach. Qualitative research aims to explain a phenomenon in depth and is carried out by collecting data in as much depth as possible, which is used to describe clearly and in detail literacy skills in solving trigonometry problems in terms of gender. Data collection techniques use test and interview techniques. Based on the results of research on mathematical literacy abilities in solving trigonometry problems in terms of gender, it was found that male students were able to fulfill mathematical literacy abilities in the indicators of formulating, applying, interpreting, and evaluating, while female students fulfilled mathematical literacy abilities in the indicators of formulating and applying. Keywords: Gander, Literacy, Trigonometry